2005
DOI: 10.1002/j.1556-6678.2005.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Model of Effects of Adult Attachment on Emotional Empathy of Counseling Students

Abstract: The effects of adult attachment on emotional empathy were investigated using a sample of master's-degree level counseling students. Through structural equation modeling, the authors found that the latent attachment dimensions of avoidance and anxiety work in tandem in their effects on empathy. Lower avoidance and higher anxiety were associated with highest levels of empathy. Results are discussed in terms of attachment theory and the wounded healer concept, with implications for counselor trainees, counselor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 33 publications
4
31
1
6
Order By: Relevance
“…However, the negative association between PACES empathy and parents' attachment anxiety did not reach significance (p = .10), adding to the conflicting findings reported by Wei et al (2011). It is possible that attachment anxiety allows some individuals to empathize more deeply with others' emotional distress if they are able to draw upon shared negative emotional experiences (Trusty, Ng, & Watts, 2005), but for other anxious individuals, personal distress may inhibit empathy if they become dysregulated (Mikulincer & Shaver, 2005). In other words, self-regulation is likely an important mediator in the association between attachment anxiety and empathy, pointing to an area for further study.…”
Section: Discussioncontrasting
confidence: 68%
“…However, the negative association between PACES empathy and parents' attachment anxiety did not reach significance (p = .10), adding to the conflicting findings reported by Wei et al (2011). It is possible that attachment anxiety allows some individuals to empathize more deeply with others' emotional distress if they are able to draw upon shared negative emotional experiences (Trusty, Ng, & Watts, 2005), but for other anxious individuals, personal distress may inhibit empathy if they become dysregulated (Mikulincer & Shaver, 2005). In other words, self-regulation is likely an important mediator in the association between attachment anxiety and empathy, pointing to an area for further study.…”
Section: Discussioncontrasting
confidence: 68%
“…That is, as theory suggests, attachment security was found to be positively related to dispositional empathy, whereas avoidance of intimacy and anxiety over abandonment were found to be negatively associated with dispositional empathy (e.g., Britton & Fuendeling, 2005;Joireman, Needham, & Cummings, 2001;Trusty, Ng, & Watts, 2005). High avoidance was also found to be negatively related to empathy for the bereaved following the September 11th attacks, whereas a curvilinear relationship was uncovered between anxious attachment and empathy, with people scoring in the middle of the attachment anxiety continuum reporting greater empathy for the bereaved than those scoring at the lower or higher ends (Wayment, 2006).…”
Section: Attachment and Empathymentioning
confidence: 94%
“…Thus, it is the perception rather than actual recollections that Adlerians consider to be vital to assessment and treatment (Clark, 2002;Singer & Salovey, 1993). Research has demonstrated relationships between early childhood recollections and individual self-efficacy, current style of life, and coping styles (Chandler, 1986;Chandler & Willingham, 1986;Dinter, 2000;Kern, Gfroerer, Summers, Curlette, & Matheny, 1996;Trusty, Ng, & Watts, 2005). However, we could find no research addressing perceived early childhood family influence and chronic pain.…”
Section: Perceived Early Childhood Family Influencementioning
confidence: 90%